Mountain climbing of the grown-up patient with non-corrected congenital heart defect - Haponiuk, Ireneusz; Gierat-Haponiuk, Katarzyna; Szalewska, Dominika; Niedoszytko, Piotr; Bakuła, Stanisław; Chojnicki, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Congenital heart defects (CHD) are the cause of reduced physical performance. The presence of congenital abnormalities in the heart of grown-up patients contributes to excessive hypokinesia. We present endurance parameters and a personalized comprehensive cardiac rehabilitation program before an extreme mountain climbing of a 27-year-old patient with an uncorrected ventricular septal defect (VSD). A 26-year-old female patient with an uncorrected congenital VSD was admitted to the department of cardiac rehabilitation before the planned high-mountain expedition. Professional preparation and assessment of actual exercise capacity was performed before scheduled extreme climbing. We conclude that physical activity associated with a heavy load in people with uncorrected CHD who have not developed pulmonary hypertension and reverse right-to-left flow seems to be safe, while participation of grown-up patients with congenital heart disease (GUCH) in extreme mountain climbing requires special preparation, individually designed endurance training and education program, conducted by the team of professionals in specialist centers.